Advanced exergo-economic schemes and optimization for medium–low grade waste heat recovery of marine dual-fuel engine integrated with accumulator. (15th December 2020) - Ouyang, Tiancheng; Su, Zixiang; Zhao, Zhongkai; Wang, Zhiping; Huang, Haozhong
Graphical abstract: Highlights: Advanced exergo-economic scheme for waste heat recovery of marine engine is proposed. The best matching mode is determined by comprehensive analysis and comparison. A heat accumulator is installed to cope with fluctuating heat sources. The optimal exergy-economic condition is obtained by multi-objective optimization. The power and thermal efficiency of engine system are increased by 13.81% and 4.66%. Abstract: Facing the multiple pressures of energy reserves decline, ecological environment deterioration and transportation industry prosperity, in order to enhance the marine performance, improve the enterprises economic benefits, and achieve the purpose of energy conservation and emission reduction, the revolution of green and efficient waste heat recovery technology is imperative. Therefore, the exergy-based configuration design of marine cascade waste heat recovery system is proposed, including supercritical Brayton cycle, organic Rankine cycle, organic flash cycle, organic trilateral cycle and absorption refrigeration cycle. Firstly, the mathematical models of three cycle-configurations are established based on thermodynamic equations, and the authority of simulation results is preliminarily verified. Then, the relationship between working-fluid, matching mode and operation parameters with cycle-configuration performance is analyzed in turn. After the multi-objective optimization, the thermodynamic performance and economic benefits of the cycle-configuration are comprehensively evaluated. Finally, the positive influence of the accumulator on the refrigeration system is explored. The numerical results prove that the proposed cycle-configuration has significant thermodynamic performance and economic benefits, reflects the good performance of energy saving and emission reduction, and can eliminate the negative impact of latent heat fluctuation on the refrigeration system. It provides a feasible idea for researchers and manufacturers who are committed to comprehensively improve the performance of cascade waste heat recovery, and fills the research gap in the latest investigation.